Circularly Polarized Split Ring Resonator Loaded Slot Antenna - Parvathy, A. R.; Ajay, V. G.; Thomaskutty, M. (Advanced Electromagnetics, 2018)
A compact circularly polarized printed slot antenna operating at 2.45 GHz is reported. The antenna consists of a pair of rotated square split ring resonators (SRR) inside a rectangular slot etched on the ground plane of an FR-4 dielectric substrate. A microstrip open-loop feed is etched on the backside of the dielectric substrate to feed the slot and the split ring resonators. The overall size of the antenna is 60x42x1.6 mm3. The measured -10dB impedance bandwidth is 10.48% (2.38-2.64 GHz) and the measured 3dB axial ratio (AR) bandwidth covers the entire impedance bandwidth.